1989
DOI: 10.1037/0022-006x.57.6.692
|View full text |Cite
|
Sign up to set email alerts
|

Controlled prospective longitudinal study of women with cancer: II. Psychological outcomes.

Abstract: The incidence and etiology of major life difficulties for women with survivable cancer were studied. Women with early stage cancer (n = 65) were assessed after their diagnosis but prior to treatment and then reassessed at 4, 8, and 12 months posttreatment. Two matched comparison groups, women diagnosed and treated for benign disease (n = 22) and healthy women (n = 60), were also assessed longitudinally. Results for four life areas are reported: (a) The emotional response to the lifethreatening diagnosis and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
138
2
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 26 publications
10
138
2
2
Order By: Relevance
“…Here, "survivor" was operationalized as a patient who was at least 6 months post any cancer therapy and diagnosed 2−10 years previously as the clinically relevant interval for the study aims. By at least 2 years, the acute stress of diagnosis has ended (Andersen, Anderson, & deProsse, 1989b), patients have returned to their pre-cancer routines (Guidozzi, 1993;Klee, Thranov, & Machin, 2000a, b), and sexual changes have stabilized (Andersen et al, 1989a). By excluding patients treated longer than 10 years previously, we hoped to decrease the likelihood of added, comorbid conditions common in older adulthood that also disrupt sexuality (Lethbridge-Cejku, Schiller, & Bernadel, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Here, "survivor" was operationalized as a patient who was at least 6 months post any cancer therapy and diagnosed 2−10 years previously as the clinically relevant interval for the study aims. By at least 2 years, the acute stress of diagnosis has ended (Andersen, Anderson, & deProsse, 1989b), patients have returned to their pre-cancer routines (Guidozzi, 1993;Klee, Thranov, & Machin, 2000a, b), and sexual changes have stabilized (Andersen et al, 1989a). By excluding patients treated longer than 10 years previously, we hoped to decrease the likelihood of added, comorbid conditions common in older adulthood that also disrupt sexuality (Lethbridge-Cejku, Schiller, & Bernadel, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Sexual problems can have an additive, negative effect on physical and psychological health of individuals with cancer and their partners [5]. Aging may exacerbate or ameliorate these problems; cancer survivors can feel uncertain about whether sexual problems are a consequence of cancer or aging [6].…”
Section: Introductionmentioning
confidence: 99%
“…These data were encouraging as they were the first tests of covariation of emotional distress and one general measure of immune status in cancer patients prior to their treatment. Also, the subscales that the prospective longitudinal study had indicated as relevant for women with cancer (Depression and Confusion; Andersen, Anderson, & deProsse, 1989b) were also relevant for the prediction of WBC counts.…”
Section: Biological Pathwaysmentioning
confidence: 99%
“…These data were encouraging as they were the first tests of covariation of emotional distress and one general measure of immune status in cancer patients prior to their treatment. Also, the subscales that the prospective longitudinal study had indicated as relevant for women with cancer (Depression and Confusion; Andersen, Anderson, & deProsse, 1989b) were also relevant for the prediction of WBC counts.More recent data replicated and extended these findings (Roberts, Andersen, & Lubaroff 1994). Subjects were women with cervical (Stage I, n = 27; Stage II, n = 10) or endometrial (Stage I, n = 17; Stage II, n = 4) cancer assessed on two occasions (separated by approximately one week) following their diagnosis and prior to treatment.…”
mentioning
confidence: 99%